Income Statement CV. Source Makmur Pratama Indonesia for the 2021 Period - Glory, Ruth (Indonesian Operations Research Association (IORA), 2021)
Financial statements are one of the important components in the development of a company. However, there are still companies that do not make financial statements according to the applicable rules. This report was prepared with the intention of helping CV. Sumber Makmur Pratama Indonesia in the preparation of good financial statements and analysis of the financial statements made. The financial statements made are income statements with descriptive analysis research methods. The preparation is done by collecting data, determining the accounts to be used, knowing the format to be presented, and including the three main components in the income statement. After the income statement was prepared, a net profit of IDR 632,218,514.50 was obtained and the results of ratio analysis showed that CV. Sumber Makmur Pratama Indonesia has a good turnover of goods and company effectiveness. Hopefully, this report will be useful for CV. Sumber Makmur Pratama Indonesia and other readers in compiling and analyzing company finances that can be useful in making company decisions.